An in-depth investigation of 11 pulsars discovered by FAST. Issue 3 (14th May 2020) - Cameron, A D; Li, D; Hobbs, G; Zhang, L; Miao, C C; Wang, J B; Yuan, M; Wang, S; Jacobs Corban, G; Cruces, M; Dai, S; Feng, Y; et al.
ABSTRACT: We present timing solutions and analyses of 11 pulsars discovered by the Five-hundred-meter Aperture Spherical radio Telescope (FAST). These pulsars were discovered using an ultrawide bandwidth receiver in drift-scan observations made during the commissioning phase of FAST, and were then confirmed and timed using the 64-m Parkes Radio Telescope. Each pulsar has been observed over a span of at least one year. Highlighted discoveries include PSR J0344−0901, which displays mode-changing behaviour and may belong to the class of so-called swooshing pulsars (alongside PSRs B0919+06 and B1859+07); PSR J0803−0942, whose emission is almost completely linearly polarized; and PSRs J1900−0134 and J1945+1211, whose well-defined polarization angle curves place stringent constraints on their emission geometry. We further discuss the detectability of these pulsars by earlier surveys, and highlight lessons learned from our work in carrying out confirmation and monitoring observations of pulsars discovered by a highly sensitive telescope, many of which may be applicable to next-generation pulsar surveys. This paper marks one of the first major releases of FAST-discovered pulsars, and paves the way for future discoveries anticipated from the Commensal Radio Astronomy FAST Survey.